2021
DOI: 10.3389/fcell.2021.615928
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Induced Gut Microbiota Alterations Associating With Ghrelin/Jak2/Stat3 Up-Regulation to Promote Benign Prostatic Hyperplasia Development

Abstract: The role of high-fat diet (HFD) induced gut microbiota alteration and Ghrelin as well as their correlation in benign prostatic hyperplasia (BPH) were explored in our study. The gut microbiota was analyzed by 16s rRNA sequencing. Ghrelin levels in serum, along with Ghrelin and Ghrelin receptor in prostate tissue of mice and patients with BPH were measured. The effect of Ghrelin on cell proliferation, apoptosis, and induction of BPH in mice was explored. Our results indicated that BPH mice have the highest ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…This suggests that the occurrence and development of BPH may be strongly correlated with the alteration of Bacteroidetes and Firmicutes . Another study has reported that gut microbiota may be associated with ghrelin which plays an important role in activation of JAK2/STAT3 in BPH development, indicating ghrelin might be pathogenic factors for BPH and could be used as a target for mediation [ 48 ]. As we all know, ghrelin is a gastric hormone which could be affected by metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the occurrence and development of BPH may be strongly correlated with the alteration of Bacteroidetes and Firmicutes . Another study has reported that gut microbiota may be associated with ghrelin which plays an important role in activation of JAK2/STAT3 in BPH development, indicating ghrelin might be pathogenic factors for BPH and could be used as a target for mediation [ 48 ]. As we all know, ghrelin is a gastric hormone which could be affected by metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2/ STAT3 pathway is one of the important signal transduction pathways of various cytokines and growth factors in mammalian bodies. Gu et al found that it could promote prostatic gland and interstitial hyperplasia by activating JAK2/STAT3 pathway (Gu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…80 On the other hand, gut dysbiosis, particularly an increased abundance of Firmicutes and Bacteroidetes, may upregulate ghrelin, thereby promoting cell proliferation and inhibiting apoptosis. 81 In addition, metabolites of gut microbiota such as SCFAs, amino acids, formyl peptides, lipopolysaccharides, and hydrogen sulfide regulate ghrelin in a direct or an indirect manner. 82 For example, SCFAs can attenuate ghrelin-mediated signals, such as ghrelin-dependent mobilization of intracellular calcium.…”
Section: Ghrelinmentioning
confidence: 99%